Riverine Calcium End-Members Improve Coastal Saturation State Calculations and Reveal Regionally Variable Calcification Potential - Beckwith, Sean T.; Byrne, Robert H.; Hallock, Pamela (Frontiers in Marine Science, 2019)
Carbonate-rich groundwater discharged from springs, seeps, and spring-fed rivers on carbonate platforms creates environments of potential refuge for calcifying organisms in coastal waters by supplying higher [Ca2+] and [CO32-] along with typically lower nutrient concentrations. The benefits associated with carbonate terrains are maximized in the presence of submerged aquatic vegetation, especially seagrasses. To improve the accuracy of carbonate saturation state (Ω) determinations, calculated values of [CO32-] and Ksp* were paired with [Ca2+] values determined using a model that incorporates directly measured riverine calcium end-members (model A). This model results in Ω values larger than those calculated by assuming that [Ca2+] is directly proportional to salinity (model B; e.g., using CO2SYS, CO2calc). As an example, for salinity (S) between 13.5 and 24, improvements in saturation states calculated as differences (ΔΩ) between model A and model B saturation states in the tidal mixing zone of the Weeki Wachee River (Florida, USA) ranged from 0.39–1.00 (aragonite) and 0.61–1.65 (calcite). Saturation state ratios (Ω(A)/ Ω(B)) for coastal waters with enhanced [Ca2+] originating from carbonate-rich groundwater can be calculated from end-member calcium concentrations and salinity. Applied to several river systems in the conterminous United States, Ω(A)/ Ω(B) values calculated at S = 20 lead to Ω(A)/ Ω(B) ratios of 1.12 (Weeki Wachee), 1.09 (Anclote), 1.06 (Mississippi), and 1.03 (Columbia). These increases in saturation states can be used to identify potential calcification refugia for subsequent high resolution field studies that focus on, for example, the long-term viability of oyster communities and other calcifying organisms in brackish coastal waters.